1998
DOI: 10.1038/bjc.1998.155
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between basic fibroblast growth factor immunostaining of stromal cells and stromelysin-3 mRNA expression in human breast carcinoma

Abstract: Summary We examined the localization of basic fibroblast growth factor (bFGF) in a series of human breast carcinomas using immunohistochemistry. Staining was observed in tumour cells in 15 out of 54 (28%) tumours and in the adjacent stroma in 34 out of 54 (63%) tumours examined. No correlation was observed between positive staining of these two compartments. The relationship between bFGF staining and expression of the metalloprotease stromelysin-3, and between bFGF and microvessel density, was examined. A stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 25 publications
0
12
0
2
Order By: Relevance
“…This is not always the case however. In one series, it was reported that in 15 of 54 (28%) breast cancer samples, the tumor cells themselves were positive, and also in the adjacent stroma, 34 of 54 (63%) samples exhibited positive staining (97). In another study, it was reported that 6 of 21 (29%) cases of pancreatic cancer expressed MMP-11 in the epithelial tumor cells with 17 of 21 (81%) cases displaying expression in the adjacent stromal cells (64).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This is not always the case however. In one series, it was reported that in 15 of 54 (28%) breast cancer samples, the tumor cells themselves were positive, and also in the adjacent stroma, 34 of 54 (63%) samples exhibited positive staining (97). In another study, it was reported that 6 of 21 (29%) cases of pancreatic cancer expressed MMP-11 in the epithelial tumor cells with 17 of 21 (81%) cases displaying expression in the adjacent stromal cells (64).…”
Section: Discussionmentioning
confidence: 97%
“…We have also observed adjacent staining of malignant stromal cells in 22 of 75 (29%) of cases. In vitro studies in fibroblasts have demonstrated that basic fibroblast growth factor and epidermal growth factor can act as potent inducers of MMP-11 expression (18,97). Pancreatic cancer cells are known to over-express these growth factors; therefore, these may stimulate the expression of MMP-11 in pancreatic cancer (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…(Lefebvre et al, 1992;Wolf et al, 1993;Lefebvre et al, 1995;Maquoi et al, 1997). Expression of stromelysin-3 has been found in both invasive cells (trophoblast giant cells and possibly osteoblasts) (Lefebvre et al, 1995), as well as in stroma surrounding invasive cells (as in the case of carcinomas) (Linder et al, 1998). In the current study, we show that in late murine placenta stromelysin-3 is present in the invasive trophoblast cells, as well as in decidual stroma undergoing invasion.…”
Section: Trophoblast/stromal Cooperation In Decidual Remodelingmentioning
confidence: 99%
“…The mechanisms that induce protease expression in stromal fibroblasts are not well understood. FGF-2 (fibroblast growth factor-2) immunostaining correlates to uPA and stromelysin-3 expression in breast cancer (Visscher et al, 1995;Linder et al, 1998). In vitro studies have demonstrated that FGF-1 and FGF-2, EGF, PDGF-BB and IFN-γ and IL-1 are capable of inducing uPA expression in human fibroblasts (Michel and Quertermous, 1989;BhatNakshatri et al, 1998;Sieuwerts et al, 1999).…”
mentioning
confidence: 99%